A experiência do espaço público. Paisagem, urbanismo, arquitectura e design. - Bruno Miguel da Rocha Correia (2013)
The Public Space Experience: Landscape, Urbanism, Architecture and Design. This dissertation reports a series of field trips to different pieces of architecture that are intended to illustrate the topic of Public Space in a critical and personal way. This topic is split into four points: Landscape Urbanism, Architecture and Design. As a first approach, and in order to demystify the subject of Public Space, some writings have been selected and collected, belonging to several authors who contributed a lot towards the improvement and clarification of the definition of Public Space. Among them we can highlight Manuel de Solà-Morales, Fernando Tavora, Carlo Aymonino, Bruno Fortier and Rafael Moneo. After the first approach, the main subject has been divided into different parts, each with a different context and type, in order to make it possible to classify these parts. This way we are able to realize how important Public Space is, as structure, to society and its development. In the second phase the narrative takes place. The details of the journeys, routes and architecture masterpieces, which form the different study cases, can be read here. The selection of the multiple study cases is based on current and important architectural landmarks in the national and international scenery such as: the Reconstruction Project of the Chiado by the architect Álvaro Siza, the Aveiro University Campus Project by the architect Nuno Portas or the Requalification Project for the Historical Center of Guimarães City by the architect Fernando Távora.